Multivariate optimization of a method for the determination of fatty acids in dental biofilm by GC-MS - Roth, Simon R; Henkel, Kerstin; Altenburger, Markus J; Auwärter, Volker; Neukamm, Merja A (Bioanalysis, 2018)
Phospholipid fatty acid methyl ester (FAME) analysis offers a simple option additionally to 16S rRNA sequencing to characterize microbial communities and to monitor changes. A method was established for the characterization of dental plaque via FAME profiles. Fatty acids were determined as FAMEs (direct, acidic transesterification) and analyzed by GC-MS using an optimized temperature gradient. The transesterification reaction was optimized using a fractional factorial central composite face-centered design. Optimal conditions for the transesterification in methanol/toluene: hydrochloric acid concentration 2% ( ), reaction time 40 min, temperature 110 °C. Method validation showed satisfactory accuracy, precision and linearity. The method provides a useful tool to characterize plaque via FAME profiles and was successfully applied to samples from ten subjects demonstrating its applicability.